열탄화법을 사용한 탄화규소 나노와이어의 성장 - 노대호; 김재수; 변동진; 양재웅; 김나리 (한국재료학회, 2003)
SiC nanowires were synthesized by carbothermal reduction using metal catalysts. Synthesized nanowires had mean diameters of 30~50 nm and several mm length. The kind of catalysts affects form of SiC nanowire because of difference of growth mechanisms. These differences were made by catalyst's physical property and relative activities to the source gas. Ni acted a conventional catalyst of VLS growth mechanism. But, Case of Fe, SiC nanowire was grown by stable VLS growth mechanism without relation of growth conditions. SiC nanowire was grown by two step growth model using Cr catalyst. Conversion ratios to the SiC nanowire were increased with growth conditions. Case of Cr, conversion ratio was about 45% that was higher than other catalyst used. This high conversion ratio was obtained by the addition VS growth to radial direction on the as-grown nanowires.